The significance of coastal landscape characters among locals and tourists: a case study of Gebeng –Kuala Terengganu tourism route - Zulkifli, Nabilah Huda; Ibrahim, Putri Haryati; Zakariya, Khalilah (Kulliyyah of Architecture and Enviromental Design, International Islamic University Malaysia, 2020)
The coastal area is often promoted in tourism for its natural scenery of the sand, sea and the sun. In Malaysia, most coastal tourism attractions are located near the rural areas and are accessible via the roadways. Through a rural route, tourists have theopportunity to experience the rural landscapes and natural attractions, traditional villages, taste the local food and conduct recreational activities. However, for a route that has not been recognised as a tourism route, the attractions and landscape features are usually sparsely located and lack integration. Consequently, the interesting places along the route are not well highlighted to the locals and tourists. This study examines the Gebeng –Kuala Terengganu coastal route as a case study to identify the significant coastal landscape characters that have potentials to be enhanced for tourism. From the questionnaire surveys responded by 200 people comprising of locals, domestic tourists and international tourists, the findings revealed that recreational activities, infrastructure, accessibility, rural culture and traditional architecture are the most significant criteria for a rural coastal route. The presence of these criteria is fundamental to the development of the coastal route for tourism.